- Uji Efektivitas Daun Kelor Terhadap Shigella Dysenteriae: Uji Efektivitas Daun Kelor Terhadap Shigella Dysenteriae - Karo, Mellinia Alpatri Br; Ferdinanda, Fransiska; Natali, Oliviti; Nasution, Sri Wahyun (Biospecies, 2021)
Diarrheal disease is a disease that often occurs in developing countries and one of the factors causing the incidence of diarrhea is the bacteria Shigella dysenteriae. Moringa oleifera Lamk leaves contain alkaloid compounds, tannins, saponins, flavonoids, triterpenes / steroids, and polyphenols which are reported to have high antimicrobial and antioxidant activity. This study aims to measure the effectiveness of Moringa oleifera Lamk leaf extract in inhibiting the growth of Shigella dysentriae. This study uses a Post-Test Only Control Group Design research design and uses the disc diffusion method where the extract on MHA media has been inoculated with Shigella dysentriae bacteria. The data taken is primary data, namely the inhibition zone formed at a concentration of 15%, 30%, 45 %, 60%, 75%. The test results have shown that Moringa oleifera Lamk leaves can inhibit bacteria at a concentration of 75% with an average inhibition zone of 91.1 mm.